Knowledge, attitude and practice (KAP) of drug disposal among patient in Pusat Perubatan Universiti Kebangsaan Malaysia - Mohd Hatta, Muhammad Najmi Munawwar; Abdul Samat, Siti Nurhafizah (2017)
The knowledge, attitude and behavior of patients toward drug disposal have been observed. This study focused on patients" knowledge on drug disposal concurrent to PPUKM drug return programme. This research was carried out at outpatient pharmacy of PPUKM from 1st December 2016 till 1st January 2017. Our subject were patients of outpatient pharmacy of PPUKM. We distributed the questionnaire to random samplings and asked them to answer 23 questions including demographic questions. We managed to collect 1025 answered questionnaire during the range of time. The raw data were analyzed using SPSS. We also used the drug return data from Microsoft Excel that have been updated each month by the pharmacist to help our research. We predicted that more than half respondents know well about proper drug disposal and they use this programme as one of their alternative to dispose their medications safely. This research then will be used by outpatient pharmacy in PPUKM to improve their service and utilize their system properly.